La raccolta dei volgarizzamenti delle opere storiografiche nel manoscritto francese 688 della Biblioteca Nazionale di Parigi - Kujawiński, Jakub (Firenze University Press, 2010)
The article offers a detailed summary of my doctoral thesis "Wernakularna kolekcja historiograficzna z rękopisu francuskiego nr 688 z Biblioteki Narodowej w Paryżu. Studium źródłoznawcze" ("A Vernacular Historiographical Miscellany in the French MS 688 from the National Library in Paris. A critical study"), Adam Mickiewicz University, academic year 2009/2010, and originally made a part of the dissertation (pp. 521-527)
Keywords: Historiografia średniowieczna; Medieval historiography; Tłumaczenia średniowieczne; Medieval translations; Rękopisy średniowieczne; Manuscript Studies; Krytyka tekstu; Textual criticism; Andegaweni (dynastia); Angevins (dynasty); Włochy średniowieczne; Medieval Italy